Extra Pancreatic Necrotic Volume: Can It Prognosticate Acute Necrotising Pancreatitis- A Prospective Study - Rinoy Ram Anandan; Santosh Patil; Rupa Renganathan; Rajesh Kumar Varatharajaperumal; Rajkumar Ramasamy; Venkatesh Kasi Arunachalam (Thieme Medical and Scientific Publishers Pvt. Ltd., 2020)
Background Acute necrotizing pancreatitis (ANP) is associated with higher mortality and morbidity. We need a method which is accurate in predicting the prognosis, and when applied early in the disease process, can help in closer monitoring and early initiation of treatment for at-risk patients. Objectives The aim of this prospective study was to assess the extra pancreatic necrosis (EPN) volume in patients with ANP and compare it with outcome variables such as organ failure, death and need for intervention as well as to compare the predictive power of EPN volume with modified CT severity index (CTSI). Materials and Methods The study had 48 patients with clinical diagnosis of acute pancreatitis, who underwent Contrast enhanced CT (CECT) between 3-6 days of onset. In all these patients, EPN volume (in cubic centimetre) and modified CTSI score were calculated and compared with the patient outcome parameters such as duration of hospital/ICU stay, need for percutaneous/surgical intervention, evidence of infection and organ failure. The results were compared with assess the predictive power of EPN volume. Statistical analysis The analysis was done in SPSS version 16.0 for windows. Pearson Correlation was used to assess the significant relationship between selected objective variables. Results EPN volume (>/= to 360 cc) had a statistically significant correlation with outcome parameters as well as in predicting overall organ failure. In our study, Modified CTSI had no significant correlation with the above mentioned factors. Conclusions The volume of EPN calculated between 3rd and 6th day of onset of symptoms showed a significant correlation with the outcome in patients with ANP.